Integration of Rahmatan Lil 'Alamin Valuesin Early Childhood Learning - Puspitasari, Nita; Rofi'ah, Siti Hamidahtur; Ansori, Muhammad; Istiqomah, Rofiatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The case of elementary school students' involvement in acts of intolerance in several regions in Indonesia demonstrates the importance of early radicalism prevention. Early childhood education is a strategic space for instilling values​​of tolerance and compassion from the beginning of development. This study aims to describe the integration of Rahmatan lil 'alamin values​​through the Manaqib program of Sheikh Abdul Qadir Jailani at Al-Qodiri Kindergarten in Jember as a strategy for preventing early radicalism. The research method uses a qualitative approach with a case study type. Data were collected through observation, interviews, and analysis of learning documents. The results show that the Manaqib activity is carried out through three steps: collective dhikr to build spirituality and peace of mind, storytelling of the story of Sheikh Abdul Qadir Jailani to instill examples of compassion, care, and respect for differences, as well as habituation and role models of teachers in daily practice. The integrated rahmatan lil 'alamin values​​are ta'addub, qudwah, muwatanah, tawassut, musawah, and tasamuh. Changes are seen in children's behavior, which is friendlier, more open, empathetic, and avoids discriminatory attitudes